1990
DOI: 10.1007/bf00300786
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the mode of action of prostaglandin E2 (PGE2) and sulprostone, a PGE2-derivative, on the lower urinary tract in healthy women

Abstract: The influence of intravesical administration of PGE2 (1,500 micrograms) and sulprostone, a PGE2 derivative (1,000 micrograms) on urodynamic parameters of the lower urinary tract was tested on six healthy female patients. PGE2 and sulprostone significantly decreased the urethral closure pressure at rest. PGE2 increased the detrusor opening pressure as well as the detrusor pressure during maximum flow. Sulprostone, in contrast, slightly decreased these parameters. Both substances caused a strong urgency sensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 15 publications
4
48
0
Order By: Relevance
“…3 Intravesical administration of PGE2 stimulated reflex micturition in human and rats, while administration of EP1 receptor antagonist improved bladder storage function in rats. [4][5][6] These studies indicated the involvement of PGE2 via EP1 receptor in urinary frequency. There is a report that intravenous administration of EP1 antagonist relieved bladder pain in cystitis model rats.…”
Section: Textmentioning
confidence: 84%
“…3 Intravesical administration of PGE2 stimulated reflex micturition in human and rats, while administration of EP1 receptor antagonist improved bladder storage function in rats. [4][5][6] These studies indicated the involvement of PGE2 via EP1 receptor in urinary frequency. There is a report that intravenous administration of EP1 antagonist relieved bladder pain in cystitis model rats.…”
Section: Textmentioning
confidence: 84%
“…A more important physiologic role might be sensitization of afferent nerves. PGE2 instillation into the bladder produces DO, both in humans 81 and animals. 82 Evidence for an involvement of different prostanoid receptors (EP1, EP3, IP) in afferent signaling has been presented, 83 -86 making these receptors interesting drug targets.…”
Section: Local Mediators Influencing Spontaneous Activitymentioning
confidence: 99%
“…In humans, PGE 2 administration into the urinary bladder caused a strong sensation of urgency (27). It was speculated that PGE 2 reduced bladder capacity and increased bladder instability (27).…”
mentioning
confidence: 99%
“…In humans, PGE 2 administration into the urinary bladder caused a strong sensation of urgency (27). It was speculated that PGE 2 reduced bladder capacity and increased bladder instability (27). Other studies have indicated that PGE 2 affects bladder smooth muscle directly, and activates capsaicin-sensitive bladder afferent (18,19).…”
mentioning
confidence: 99%